Change of Direction in Understanding the History of Education in Slovakia in the 1940s - Blanka Kudláčová (Charles University, 2018)
Abstract: The paper is a historical-educational study that aims to survey changes in the conceptual foundations of the field of the history of education in the 1940s, when a change of direction in its understanding, caused mainly by political circumstances, occurred. It was a complicated period with several overlapping ideological levels: the ideas of the interwar democratic Czechoslovakia "retired", the national socialist ideology of the Slovak state was established in the situation of the war, and the Marxist-Leninist ideology, which was fully implemented after the communist coup in 1948, was being gradually shaped. A change of direction in the history of education and a change in its foundations will be demonstrated via two leading figures in the pedagogy of the period and their historical-educational work. Th e first one is Juraj Čečetka (1907-1983), the first Slovak professor of pedagogy. In 1940, he published his work Zo slovenskej pedagogiky [From Slovak Pedagogy], which can be considered the first Slovak scientific publication in the fi eld of the modern history of education. The second personality that signifi cantly infl uenced the character of pedagogy in Slovakia in the 1940s was Ondrej Pavlík (1916-1996). Th e conceptual foundations of his writings were different in comparison to Čečetka's work and his successful establishment was aided by political engagement. His pedagogical work was predetermined by a dissertation thesis, Vývin sovietskeho školstva a pedagogiky (1945) [Development of Soviet Education and Pedagogy], and a monograph, Vysoké školy v Sovietskom zväze (1947) [Universities in the Soviet Union]. Discussing the work of Juraj Čečetka and Ondrej Pavlík, the following can be pointed out: 1. the close connection between personal conviction and political engagement and scientific work; 2. the impact of the ideology of totalitarian regimes on science and education, and 3. a change of direction in the understanding of the history of education under the influence of totalitarian ideologies and the difficulty of evaluating them objectively. Keywords: history of education, national socialist ideology, Marxist-Leninist ideology, Juraj Čečetka, Ondrej Pavlík.